Evaluation of Liquid Smoke’s Use on Beef Meatballs Through The Hedonic Approach - M., Silaban; Miwada, I N.S; Lindawati, S. A (Jurnal Peternakan Tropika, 2018)
This study aims to determine the concentration of liquid smoke that is appropriate to be used in the manufacture of beef meatballs which taste smoke by identifying the response of panelists to smoke meatballs. This research was conducted at the Animal Husbandry and Microbiology Technology Laboratory, Faculty of Animal Husbandry, Udayana University located at Jalan P.B Sudirman, Denpasar.  This study lasted for two months. The beef meatballs used in this study were obtained from PT. The smell of Rasaprima Ambassadors located on Jalan By Pass Ngurah Rai No. 555x, Denpasar, Bali, Indonesia, amounting to 1 kg.  Liquid smoke that is used is special liquid smoke from food obtained from distillation or condensation of coconut shell steam.  This liquid smoke is obtained from liquid smoke companies located in Jember, East Java.  The study design used a simple randomized complete design (RAL) with five treatments which included P1 (concentration of liquid smoke 0%), P2 (concentration of liquid smoke 0.5%), P3 (concentration of liquid smoke 1.0%), P4 (concentration liquid smoke 1.5%), and P5 (concentration of liquid smoke 2.0%).  The variables observed in this study include the value of organoleptic test.  Data analysis in this study used Non-Parametric analysis (Kruskal-Wallis), if there were significant differences between treatments (P <0.05), then continued with the Mann Whitney Test with the help of SPSS 16.0 program.  The results of the evaluation of the use of liquid smoke in beef meatballs through this hedonic indicator approach showed a significant effect (P <0.05) on the variable of aroma compared to other variables such as color, texture, flavor, and overall acceptance. Based on the results of this study it can be concluded that the concentration of liquid smoke is 0.5% and 1.5% which is most acceptable to the panelist senses to changes in the concentration of liquid smoke.   Keywords: Liquid Smoke, Concentration, Beef Meatballs, Panelists